CTCF is selectively required for maintaining chromatin accessibility and gene expression in human erythropoiesis - Xue Yang; Li Cheng; Ye Xin; Jianxiang Zhang; Xinfeng Chen; Jinchao Xu; Mengli Zhang; Ruopeng Feng; Judith Hyle; Wenjie Qi; Wojciech Rosikiewicz; Beisi Xu; et al. (Genome Biology)
Abstract Background CTCF is considered as the most essential transcription factor regulating chromatin architecture and gene expression. However, genome-wide impact of CTCF on erythropoiesis has not been extensively investigated. Results Using a state-of-the-art human erythroid progenitor cell model (HUDEP-2 and HEL cell lines), we systematically investigate the effects of acute CTCF loss by an auxin-inducible degron system on transcriptional programs, chromatin accessibility, CTCF genome occupancy, and genome architecture. By integrating multi-omics datasets, we reveal that acute CTCF loss notably disrupts genome-wide chromatin accessibility and the transcription network. We detect over thousands of decreased chromatin accessibility regions but only a few hundred increased regions after CTCF depletion in HUDEP-2 and HEL lines, suggesting the role of CTCF in maintaining proper chromatin openness in the erythroid lineage. CTCF depletion in the erythroid context notably disrupts the boundary integrity of topologically associating domains and chromatin loops but does not affect nuclear compartmentalization. We find erythroid lineage-specific genes, including some metabolism-related genes, are suppressed at immature and mature stages. Notably, we find a subset of genes whose transcriptional levels increase upon CTCF depletion, accompanied by decreased chromatin accessibility regions enriched with the GATA motif. We further decipher the molecular mechanism underlying the CTCF/GATA2 repression axis through distal non-coding chromatin regions. These results suggest a suppressive role of CTCF in gene expression during erythroid lineage specification. Conclusions Our study reveals a novel role of CTCF in regulating erythroid differentiation by maintaining its proper chromatin openness and gene expression network, which extends our understanding of CTCF biology.